Konsep Himpunan Fuzzy pada Paradoks Russel - Muhammad Abdy; Awi Dassa; Sri Julia Nensi (Jurusan Matematika FMIPA UNM, 2019)
Fuzzy sets use the basis of fuzzy logic to declare an object to be a member with the degree ofmembership ( ), but fuzzy logic violates the law of binary logic so that the assumption arises that fuzzylogic has the same problem with paradox. But the true value of fuzzy logic depends on the degree ofmembership it has so that a conclusion can be drawn from the large membership ranks, while the paradoxof its value cannot be drawn any conclusions. The paradox is a form of ground criticism that aims toexpress and determine the inconsistencies or contradictions that result from several mental experiments inmathematics, one of the paradoxes that is well-known in critics of set theory is Russel's paradox. The paradoxical solution of Russell by using fuzzy set theory concepts is that the degreeof membership is 0.5 and is 0.5.